ChemInform Abstract: Hydrodeoxygenation of Sulfoxides to Sulfides by a Pt and MoOx Co‐Loaded TiO2 Catalyst. Issue 34 (4th August 2016) - Touchy, Abeda Sultana; Hakim Siddiki, S. M. A.; Onodera, Wataru; Kon, Kenichi; Shimizu, Ken‐ichi
Abstract: Title catalyst is used for the dehydrogenation of sulfoxides to sulfides under solvent‐free and mild conditions.